Dynamics of resonantly excited excitons in GaN - Hess, S; Walraet, F; Taylor, R; Ryan, J; Beaumont, B; Gibart, P (1998)
We present resonant fs pump-probe reflectance measurements of excitons in wurtzite GaN epilayers at different lattice temperatures. At 4 K we find that the exciton dynamics is dominated by trapping at defects via acoustic-phonon emission on a time scale of 16 ps. At temperatures above 60 K we observe a much longer relaxation component of 375 ps, which is due to radiative recombination of free excitons. The results are in good agreement with theoretical predictions.